Fe3O4@MgO nanoparticles as an efficient recyclable catalyst for the synthesis of phosphoroamidates via the Atherton–Todd reaction. Issue 46 (18th November 2015) - Kaboudin, Babak; Kazemi, Foad; Habibi, Fereshteh
Graphical abstract: Abstract: A simple and efficient method is presented for the synthesis of phosphoroamidates in moderate to good yield via the Atherton–Todd coupling of primary amines with H -dialkyl phosphites using Fe3 O4 @MgO nanoparticles as a recyclable catalyst.